2010
DOI: 10.1186/1477-3155-8-26
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and translocation to the aerial part of magnetic carbon-coated nanoparticles through the root of different crop plants

Abstract: The development of nanodevices for agriculture and plant research will allow several new applications, ranging from treatments with agrochemicals to delivery of nucleic acids for genetic transformation. But a long way for research is still in front of us until such nanodevices could be widely used. Their behaviour inside the plants is not yet well known and the putative toxic effects for both, the plants directly exposed and/or the animals and humans, if the nanodevices reach the food chain, remain uncertain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(96 citation statements)
references
References 22 publications
3
91
0
2
Order By: Relevance
“…Previous soil-grown soybean studies regarded metal salts (33,35), but studies examining plant-MNM interactions generally used aqueous exposure systems (24,(36)(37)(38). There has been contradictory evidence from studying soil microbial communities, i.e., that some MNMs are not bioavailable in soil (39), but also evidence to the contrary for other MNMs (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous soil-grown soybean studies regarded metal salts (33,35), but studies examining plant-MNM interactions generally used aqueous exposure systems (24,(36)(37)(38). There has been contradictory evidence from studying soil microbial communities, i.e., that some MNMs are not bioavailable in soil (39), but also evidence to the contrary for other MNMs (25).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the structural integrity of plasmodesmata is maintained by cytoskeleton microfilaments and certain ENMs (ultrasmall TiO 2 nanoparticles) have been reported to disrupt such microtubular networks in Arabidopsis thaliana (Wang S. et al, 2011;Larue et al, 2012a). Additionally, Rab proteins were hypothesized to have a role directing "cargo" to specific areas near plasmodesmata locations (Cifuentes et al, 2010). As a result, the transportation of ENMs may be facilitated through the normal and coordinated activity of organelles, transport proteins and trans-wall channels.…”
Section: Symplastic Routementioning
confidence: 99%
“…Upon accumulation, particle distribution via the vasculature (Fig. 1c) could occur rapidly; ENMs were detected in shoots as short as 24 h after carbon-coated magentic nanoparticle exposure to Helianthus annuus (sunflower), Lycopersicum sculentum (tomato), Pisum sativum (pea) and Triticum aestivum (wheat) (Cifuentes et al, 2010). An in vivo plant flow cytometry assessment showed that the average velocity of linear flow in Lycopersicum sculentum stems exposed to quantum dot-carbon nanotube conjugates was approximately 0.2 mm/s .…”
Section: Translocation and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green vegetable samples shows that the iron content in the green vegetables was increased. Cifuentes et al (2010) studied absorption and translocation on the root of the plants by nano particles of iron sands [6]. Stimulation of magnetic nano particles were also performed on Tobacco BY-2 cells, which results that the magnetic nano particles stimulated affect in antioxidant elements contained in Tobacco BY-2 cells [7].…”
Section: Introductionmentioning
confidence: 99%